Prevalence of Trichomonas gallinae infection in Pigeon of Jessore District, Bangladesh - Arfin, Shamsul; Sayeed, Md Abu; Sultana, Shaharin; Dash, Amith Kumar; Hossen, Md Liakot (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: This study was conducted to estimate the prevalence of Trichomonas gallinae infection in pigeon and determination of spatial factors related with T. gallinae infection among smallholder farms at Abhaynagar and Monirampur Upazillas, Jessore District, Bangladesh. Materials and Methods: This cross-sectional study has undertaken from November 24, 2017 to February 28, 2018 on randomly selected 60 pigeons from 12 smallholder farms. Wet smear technique has been used to identify T. gallinae, from swab samples collected from oropharynx and crop of the sampled birds. Results: The overall prevalence was 60% (95% CI: 46.5–72.4) in which 75% (95% CI: 55.1–89.3), 50% (95% CI: 23.0–76.9), and 44.4% (95% CI: 21.5–69.2) were in squab, adult male, and adult female, respectively. The prevalence, in the case of dead pigeons (n = 13), 69.2% showed positive to the protozoan infection in the study. On the basis of spatial distribution, T. gallinae infection in the rural area was 64% (n = 25) followed by urban area 57.1% (n = 35) of the district. The prevalence of T. gallinae was insignificantly higher at Abhaynagar upazilla in contrast to Monirampur upazilla (30%) of Jessore district. Conclusion: This research finding suggests that a significant level of (57.4%) T. gallinae infection is circulating among the pigeon population of Bangladesh. Therefore, proper housing, feeding, and disease management should be ensured by the owner to prevent this problem. J. Adv. Vet. Anim. Res., 6(4): 549-552, December 2019